Trucks - Daynes, Katie; Fox, Christyan (London : Usborne ; Tulsa, OK : EDC, 2007)
Simple text, photographs, and illustrations describe the parts and uses of various types of trucks.
First published: 2002.
Includes index.
2.4
K-3
IG 710
Accelerated Reader AR
Keywords: Trucks -- Juvenile literature